2014
DOI: 10.7554/elife.02626
|View full text |Cite
|
Sign up to set email alerts
|

Multi-species, multi-transcription factor binding highlights conserved control of tissue-specific biological pathways

Abstract: As exome sequencing gives way to genome sequencing, the need to interpret the function of regulatory DNA becomes increasingly important. To test whether evolutionary conservation of cis-regulatory modules (CRMs) gives insight into human gene regulation, we determined transcription factor (TF) binding locations of four liver-essential TFs in liver tissue from human, macaque, mouse, rat, and dog. Approximately, two thirds of the TF-bound regions fell into CRMs. Less than half of the human CRMs were found as a CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 90 publications
12
103
3
Order By: Relevance
“…We first enumerated all CREs occupied by GATA1 in primary human EBs that are proximal to the ∼20 known pathogenic MED genes. Within these CREs, we identified 176 core GATA sites, and investigated the evolutionary conservation of these four nucleotides as a proxy for functionality (32,44,47,48). Surprisingly, although we observed only slight conservation for the GATA site within all ∼20,000 GATA1 chromatin occupancy sites across the genome, GATA sites within MED CREs were substantially conserved (Fig.…”
Section: Isogenic Cellular Models Phenocopy Cell-intrinsic Effects Ofmentioning
confidence: 95%
See 1 more Smart Citation
“…We first enumerated all CREs occupied by GATA1 in primary human EBs that are proximal to the ∼20 known pathogenic MED genes. Within these CREs, we identified 176 core GATA sites, and investigated the evolutionary conservation of these four nucleotides as a proxy for functionality (32,44,47,48). Surprisingly, although we observed only slight conservation for the GATA site within all ∼20,000 GATA1 chromatin occupancy sites across the genome, GATA sites within MED CREs were substantially conserved (Fig.…”
Section: Isogenic Cellular Models Phenocopy Cell-intrinsic Effects Ofmentioning
confidence: 95%
“…3D) (40). (9,44,47,48). This suggests the possibility that an important minority of causal genetic lesions may instead be located within NC regulatory regions.…”
Section: Isogenic Cellular Models Phenocopy Cell-intrinsic Effects Ofmentioning
confidence: 99%
“…Among these master regulators, HNF4A is essential for the differentiation of human hepatic progenitor cells (DeLaForest et al 2011). Likewise, CEBPA is required for the liver cell specification and gene function, and the associated TFBSs are highly conserved across mammals (Ballester et al 2014). Both CEBPA and HNF4A have conserved cis-regulatory activity and a large number of shared TF binding events across distant vertebrates (Schmidt et al 2010).…”
Section: Specific Transcription Factor Motifs Are Associated With Regmentioning
confidence: 99%
“…We previously found that conserved orthologous transcription factor binding can reveal functional enhancers (Ballester et al, 2014). To identify evolutionarily conserved, epigenetically modified enhancers for further functional analyses, we performed ERG ChIP-seq experiments in both human (HUVECs) and bovine (BAECs) ECs cultured in complete media (i.e.…”
Section: Erg Regulates a Network Of Constitutive And Vegf-inducible Gmentioning
confidence: 99%
“…Approximately 20 million cells were used for the ERG and ∼3 million cells for the H3K27ac ChIPs. ChIP experiments were conducted as previously described (Ballester et al, 2014). Antibodies used for ChIP were mouse anti-H3K27ac (Millipore, 05-1334 monoclonal) and rabbit anti-ERG 1/2/3 (Santa Cruz Biotechnology, sc353 polyclonal).…”
Section: Chip-seq Experiments and Analysismentioning
confidence: 99%